The Decompositioning of Volatile-Matter of Tanjung Enim Coal by using Thermogravimetry Analyzer (TGA) - Nukman, Nukman (UI Scholars Hub, 2008)
The Decompositioning of Volatile-Matter of Tanjung Enim Coal by using Thermogravimetry Analyzer (TGA). Coal is a nature material which a kind of energy source. The decompotition of coal could analyze by heat treated using thermogravimetry analyzer. The decomposition of the volatile matter for three kinds of Tanjung Enim coal could be known. The value of activation energy that be found diference, then for Semi Anthracite, Bitumonius and Sub Bituminous Coal, the initial temperatures are 60.8 oC, 70.7 oC, 97.8oC, and the last temperatures are 893.8 oC, 832 oC, 584.6oC.